ANALISIS YURIDIS PERBANDINGAN PUTUSAN NO.183/PID.SUS/2024/PN PSW DENGAN PUTUSAN NO.124/PID.SUS/2024/PN PSW MENGENAI TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA DI PENGADILAN NEGERI PASARWAJO - Ali Mustafa La Ode; Rifqah Zahra Khaidar K (Fakultas Hukum Universitas Dayanu Ikhsanuddin, 2026)
This study aims to determine the legal basis for the judge's considerations in deciding a case and what influences the differences between decision No.183/Pid. Sus/2024/PN Psw. and decision No.124/Pid. Sus/2024/PN Psw. The research method in writing this thesis is a qualitative method, with secondary and primary data coverage, this study was conducted in 1 location, namely the Pasarwajo District Court. The results of this study indicate that the legal basis for judges' considerations in a case is Law Number 48 of 2009 concerning Judicial Power, judges are responsible for conveying clear considerations and based on appropriate legal reasons, and must consider various aspects that can alleviate or burden the perpetrator. It is important for judges to pay attention to legal, philosophical, and sociological truth so that the decisions taken reflect justice and positive social impacts so that each decision can be accepted and understood by the community. The difference in verdicts handed down by judges is influenced by several factors including the facts in the trial, the role and involvement of the defendant, and the evidence found. In addition, demands from the public prosecutor and consideration of aggravating and mitigating factors are also present in the judge's decision, thus this difference in verdicts reflects the difficulties in the justice system, where each case must be considered individually based on the context and facts available, as well as the social impact of the decision taken.